IMPLEMENTATION OF CHILD DECENT CITY POLICY IN BANDA ACEH CITY (REVIEW OF QANUN NUMBER 2 OF 2021) - Indah Putri Sanura; Ria Fitri; Darmawan (RADJA PUBLIKA, 2023)
The Child Decent City Policy in Indonesia is based on Article 21 of Law Number 35 of 2014 concerning Child Protection which states that the State Government and local governments are obliged and responsible to respect the Fulfillment of Children's Rights, then Law Number 11 of 2006 concerning the government of Aceh which in its derivatives Aceh qanun number 11 of 2008 concerning Child Protection emphasizes the fulfillment of children's rights. Qanun Number 2 of 20212 concerning Child-Friendly Cities, which is a derivative of the regulation on which it is explained that the City government makes together with the Gampong government, parents, communities and community organizations in realizing development that protects children's rights. This study aims to find out how the Implementation of Banda Aceh City Qanun number 2 of 2021 concerning Child Friendly Cities, what factors affect the Implementation of Banda Aceh City Qanun number 2 of 2021 concerning Child Friendly Cities and the legal consequences of the unimplementation of Banda Aceh City Qanun number 2 of 2021 concerning Child Friendly Cities. The type of research used is empirical juridical with a statutory approach and an analytical approach, both of these approaches are needed to analyze and examine the implementation of the qanun, research sources consist of primary data sources (interviews, observations), secondary (laws, literature and other legal materials). The results of the study found that the implementation of the qanun of Banda Aceh City regarding a child-friendly city has not run well and effectively, this is influenced by several factors, the inhibiting factors consist of human resource factors, financial resource factors, leader commitment factors and policy implementation factors, while the supporting factors in the implementation of Child Decent Cities in Banda Aceh are resource factors, facilities and infrastructure, and community institution support factors. Then the legal effect of the non-implementation of the Banda Aceh city qanun concerning Child Decent Cities is administrative sanctions, although in fact the implementation of these sanctions has so far never been applied.